GO/Co-MOF/NiMnCu nanocomposite as a possible candidate for the future of the supercapacitor generations - Elham Mazaheri; Ali Bahari; Shahram Ghasemi (Progress in Physics of Applied Materials)
Some issues of the electroactive materials in supercapacitor devices, such as low specific surface area, lower electron/ion transportation, and undesirable conductivity, are threatening the current components of supercapacitor devices. Higher surface adsorption sites and specific surface area in the porous structures could contribute to the enhanced performance. The porous network facilitates higher ion diffusion, higher cyclic retention (which are not discussed in the present work) and improved electrochemical interactions. Improving these factors can cause more occupation sites, more connections between electrode-electrolyte, which means more reaction places for charge storage in the supercapacitor devices. In the present study, we synthesized graphene oxide (GO), Co- metal-organic framework (MOF) / NiMnCu nanocomposite on nickel foam (NF) (GO/ CoMOF/ NiMnCu) samples with solvothermal method. Our findings show that GO/ CoMOF/ NiMnCu sample has higher specific surface area, good porosity than their individual components. Thus, GO/ CoMOF/ NiMnCu sample has much larger specific capacitance, which can affect the sample structure and improve electrical characteristics, yield to more occupation sites and/or specific surface area, enhancement of the carrier (electrons, ions) transportation in the supercapacitor devices. Therefore, here XRD patterns confirmed metal hydroxides, Co-MOF and GO formations, and Brunauer-Emmett-Teller (BET) results revealed higher pore volume which can cause faster and better transportation of ions, or better performance of sample (GO/ CoMOF/ NiMnCu) as a possible material for the next supercapacitor devices.